Evaluation of ash‐free coal for chemical looping combustion ‐ part I: Thermogravimetric single cycle study and the reaction mechanism. (18th November 2016) - Shabani, Azar; Rahman, Moshfiqur; Pudasainee, Deepak; Samanta, Arunkumar; Sarkar, Partha; Gupta, Rajender
Abstract : In this study, performance of ash‐free coal (AFC) was evaluated for chemical looping combustion (CLC) using CuO as an oxygen carrier during reduction and oxidation processes in a thermogravimetric (TG) analyzer. TG experiments with CuO/AFC mixture with different ratios (10:1–50:1) at various temperatures ranging from 450 to 900 °C were performed and the results were analyzed in greater detail for the best suitable ratio (R30). The CLC reaction mechanism includes release of volatile matter until 450 °C and auto‐ decomposition of CuO at 790 °C. CuO reduction induced by volatile matter from AFC occurred at temperatures below 450 °C. Char combustion induced by oxygen release from CuO occurred at about 800 °C as auto‐decomposition of CuO occurs at 790 °C. A slight loss in mass, observed between 450 °C and 790 °C, is attributed to solid‐solid interaction of char and CuO powder. Advanced analytical techniques such as XRD, SEM, and ultimate analyses were employed to characterize the oxygen carrier and to understand the possible interaction of the oxygen carrier with volatile matter and char. Overall, AFC as the solid fuel showed a promising oxidation/reduction performance and has great potential to be used in the CLC process. Abstract : Schematic view of the reaction mechanism of CuO and AFC at different temperatures.